Using CAT tools in freelance translation: insights from a Case Study(1st ed.), by Paulina Pietrzak & MichalKornacki - Marina Nunes Albuquerque, Alexandra (2022)
Paulina Pietzzak and Michal Kornacki are twocomputer-assisted translation instructors at the University of Lodz, with recent but consistent research work on translator training. In Using Cat Tools in Freelance Translation: Insights from a Case Study, the authors attempt to “explore the technological evolution in translation and its effects on the process of translation” (p.1), based ona vast literature review and their previous research. Moreover,theydescribe “the demographics and attitudes of freelance translators” (p.1), whose native language is Polish,towards CAT tools,based on the findings of a survey-based study. “The study was designed to explore the attitudes and preferences of freelance translators working with various language pairs, whose native language is Polish” (p. 66). Another purpose of the study findings, although not explicit in thetitle, and therefore likely the object of a future publication,was to help the authors “identify priorities and objectives for translator training” (p. 70) as they “advocate for the implementation of the “technological toolkit” [...] in the translation classroom” (p.1)